CFD simulation of the dynamic flow behavior in a bubble column reactor - Md Hasan, Sazali (2015)
In this project report an Eulerian two-phase Computational Fluid Dynamics (CFD) model for modelling bubble columns is presented. This model is able to predict the bubbly flow parameter such as gas holdup, contact surface area, air volume fraction, pressure drop, and velocity magnitude to understanding the hydrodynamic flow behaviors. Three types of gas distributor design are tested on the 1.5 m height and 0.15 m diameter bubble column cylinder. Five different velocities are used on the each gas distributor design in order to produces a variety flow pattern in the bubble column. The ANSYS Fluent Workbench 15.0 was used as the numerical solution to make the simulation analysis on the bubble column problems. In this simulation, gas (air) is dispersed through the gas distributor into liquid (water) in the bubble column to produces the bubbles rising along the cylinder. The graphically simulation result of gas holdup and velocity profile are compare to the previous simulation result similarly tendency in shape. Quite good agreement is obtained. It observed that by increasing the superficial gas velocity, gas holdup also increases and magnitude velocity will decreases when approached the wall. From the simulation result obtained, design “c” with larger holes diameter and open area ratio mostly given the highest value of gas holdup, contact surface area, air volume fraction and magnitude velocity compare to other design. The gas distributor holes sizing will be determined the size of bubble produces. The large bubble having more buoyancy force and rise velocity compare to small bubble.